PENGARUH MODEL PEMBELAJARAN BAMBOO DANCING (TARI BAMBU) TERHADAP HASIL BELAJAR IPS SISWA SDN 1 CIPEDES - Nana Sutarna; Dian Kusdiana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2017)
This research is based on the writer's anxiety about student learning outcomes that are still under KKM. The purpose of this study to determine the effect of learning models bamboo dancing (bamboo dance) on the results of learning IPS class V SDN 1 Cipedes. Learning model of bamboo dancing (bamboo dance) and learning result are the variables studied. This research uses experimental method with quasi experimental design nonequevalent control group design that is two classes of experimental research (treated) and control (without treatment). After doing the calculations, the results of this study indicate an increase in learning outcomes IPS class V students by using learning models of bamboo dancing (bamboo dance), namely; (1) before being treated the average score of students' learning achievement of 53.49; (2) after being treated the mean value of student learning result of IPS is 82,06 and (3) the mean of posttest of experiment class is 82,06 and the mean of posttest of control class is 71,69. From the calculation result, the average value of the experimental class is better than the control class. So it can be concluded that the learning model of bamboo dancing (bamboo dance) improves the learning outcomes of IPS students of SDN 1.Cipedes.